Improving the assessment of functional impairment in tinnitus sufferers: validation of the German version of the Tinnitus Functional Index using a confirmatory factor analysis. (1st February 2022) - Hüttenrauch, Eva; Jensen, Martin; Ivanšić, Daniela; Dobel, Christian; Weise, Cornelia
Abstract: Objectives: Chronic tinnitus negatively impacts daily functioning. To specifically assess this impairment, the Tinnitus Functional Index (TFI) was developed. The current study investigated the hierarchical, eight-factorial structure for the German TFI and examined its psychometric properties. Design: In an online assessment, the TFI and other validated health-related measurements were completed. Confirmatory factor analysis (CFA) was conducted to investigate the factorial structure by testing two competing models: (1) a general factor model, and (2) a hierarchical second-order factor model. Study sample: 316 research volunteers (59.8% female) with low to moderate tinnitus distress were included. Results: CFA revealed an insufficient fit of the data to the general factor model. For the hierarchical second-order factor model, an acceptable model fit was shown (χ 2 /df ratio = 2.74, RMSEA = 0.07, SRMR = 0.05, CFI = 0.95, TLI = 0.95). Correlational analyses between the TFI and measures assessing tinnitus distress, depression, sleeping difficulties, subjective well-being, and personality dimensions indicated high convergent and moderate discriminant validity. Internal consistency reliability was excellent. Conclusions: The results confirm the hierarchical, eight-factorial structure of the German TFI. The TFI is a promising inventory that should be used on a regular basis. Highlights: The results of our study confirm the hierarchical eight-factorial structure of the German TFI. Confirmatory factor analysis revealed an acceptable model fit of the data. Convergent validity of the German TFI was high. Discriminant validity of the German TFI was moderate. The German TFI is a reliable questionnaire to assess tinnitus functional impairment.